Democratizing Philosophy: School for Life, Life for School - Charles C. Verharen (Athens Institute for Education and Research, 2020)
Re-visioning education is critical to developing new ways of thinking and acting in the face of global threats to life from global climate change and weapons of mass destruction. Like philosophy in Quine's words, education is "losing contact with the people." Education suffers this loss in part because education has lost contact with philosophy. The paper first addresses the relations between philosophy and science. Nietzsche is a primary guide on this question. While his elitism must be dismissed, his apocalyptic vision of philosophy may help students become more deeply engaged in all levels of schooling. The paper's second concern is whether philosophy can be infused into all other subjects. The conclusion considers whether it is practical to teach philosophy to all students. Schooling that democratizes philosophy can reveal that many more human beings are gifted than we could have imagined. W.E.B. Du Bois in fact argues that virtually all humans should receive higher education. A compelling reason to democratize philosophy is to further democracy itself.